2023
DOI: 10.3390/ph16040562
|View full text |Cite
|
Sign up to set email alerts
|

A Treat-and-Extend Regimen of Intravitreal Brolucizumab for Exudative Age-Related Macular Degeneration Refractory to Aflibercept: A 12-Month Result

Abstract: We aimed to investigate whether a treat-and-extend regimen of intravitreal brolucizumab (6.0 mg/0.05 mL) is effective for eyes with exudative age-related macular degeneration (AMD) refractory to aflibercept for 12 months. Sixty eyes from 56 patients receiving brolucizumab for exudative AMD refractory to aflibercept were included. Patients received a mean of 30.1 aflibercept administrations for a mean 67.9-month follow-up. All patients exhibited exudation on optical coherence tomography (OCT) despite regular 4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…The present study revealed that switching from aflibercept to brolucizumab with and without the loading dose regimen was effective in controlling retinal exudate in nAMD patients who had IRF and/or SRF under aflibercept administration at 8-week intervals. These results are consistent with previous findings in anti-VEGF treatment-resistant nAMD patients [ 12 , 13 ]. Kikushima et al reported the one-year results of switching to brolucizumab in nAMD patients who had retinal fluid after 4–8 weeks of aflibercept administration.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study revealed that switching from aflibercept to brolucizumab with and without the loading dose regimen was effective in controlling retinal exudate in nAMD patients who had IRF and/or SRF under aflibercept administration at 8-week intervals. These results are consistent with previous findings in anti-VEGF treatment-resistant nAMD patients [ 12 , 13 ]. Kikushima et al reported the one-year results of switching to brolucizumab in nAMD patients who had retinal fluid after 4–8 weeks of aflibercept administration.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the loading and nonloading groups had no visual improvement despite anatomical improvement. Improvements in anatomical outcomes without visual improvement have been reported in switching to another anti-VEGF drug [ 12 , 13 , 21 ]. We speculate that this discrepancy was due to permanent damage to photoreceptors caused by long-term disease activity and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two clinical trials for DME, KESTREL and KITE, showed non-inferiority of brolucizumab to aflibercept in terms of visual outcomes, with more study participants achieving central macular thickness (CMT) < 280 µm 11 . Although favorable real-world results of switching to brolucizumab have been reported for age-related macular degeneration in patients previously treated with anti-VEGF therapy 12 , 13 , those for DME are not available. In addition, safety signals for brolucizumab in age-related macular degeneration (AMD) have been reported in RCTs and post hoc analyses, including intraocular inflammation (IOI) and retinal vasculitis with or without vessel occlusion 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical trials for DME, KESTREL and KITE, showed non-inferiority of brolucizumab to a ibercept in terms of visual outcome, with more number of study participants achieving central macular thickness (CMT) < 280 µm [11]. Although favorable real-world results of switching to brolucizumab have been reported for age-related macular degeneration in patients previously treated with anti-VEGF therapy [12,13], those for DME are not available. In addition, safety signals for brolucizumab in age-related macular degeneration (AMD) have been reported in RCTs and post hoc analyses, including intraocular in ammation (IOI) and retinal vasculitis with or without vessel occlusion [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%